1992
DOI: 10.1002/j.1460-2075.1992.tb05301.x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of transketolase, a thiamine diphosphate dependent enzyme, at 2.5 A resolution.

Abstract: The crystal structure of Saccharomyces cerevisiae transketolase, a thiamine diphosphate dependent enzyme, has been determined to 2.5 A resolution. The enzyme is a dimer with the active sites located at the interface between the two identical subunits. The cofactor, vitamin B1 derived thiamine diphosphate, is bound at the interface between the two subunits. The enzyme subunit is built up of three domains of the alpha/beta type. The diphosphate moiety of thiamine diphosphate is bound to the enzyme at the carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
328
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 349 publications
(337 citation statements)
references
References 24 publications
8
328
1
Order By: Relevance
“…The crystal structure of this enzyme has con®rmed this observation [93,111]. While the two cofactor binding sites are identical according to the crystal structure, it has been speculated that a conserved hydrogen bonding pattern between the two ThDP molecules may facilitate cooperative interactions between the two active sites in TK [111].…”
Section: Oligomeric Structurementioning
confidence: 84%
See 4 more Smart Citations
“…The crystal structure of this enzyme has con®rmed this observation [93,111]. While the two cofactor binding sites are identical according to the crystal structure, it has been speculated that a conserved hydrogen bonding pattern between the two ThDP molecules may facilitate cooperative interactions between the two active sites in TK [111].…”
Section: Oligomeric Structurementioning
confidence: 84%
“…structures [3,30,51,93,108,111] and site-directed mutagenesis studies [18,28,171] have revealed that selected residues within the motif anchor the diphosphate group of ThDP through the divalent cation; no motif residue interacts directly with the thiazole and pyrimidine portions of the cofactor.…”
Section: Transketolase: a Thiamin Diphosphate Dependent Enzymementioning
confidence: 99%
See 3 more Smart Citations